If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7x + -1(6 + -5y + 5x) + 4y) = 0 Reorder the terms: 3(7x + -1(6 + 5x + -5y) + 4y) = 0 3(7x + (6 * -1 + 5x * -1 + -5y * -1) + 4y) = 0 3(7x + (-6 + -5x + 5y) + 4y) = 0 Reorder the terms: 3(-6 + 7x + -5x + 5y + 4y) = 0 Combine like terms: 7x + -5x = 2x 3(-6 + 2x + 5y + 4y) = 0 Combine like terms: 5y + 4y = 9y 3(-6 + 2x + 9y) = 0 (-6 * 3 + 2x * 3 + 9y * 3) = 0 (-18 + 6x + 27y) = 0 Solving -18 + 6x + 27y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 6x + 18 + 27y = 0 + 18 Reorder the terms: -18 + 18 + 6x + 27y = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 6x + 27y = 0 + 18 6x + 27y = 0 + 18 Combine like terms: 0 + 18 = 18 6x + 27y = 18 Add '-27y' to each side of the equation. 6x + 27y + -27y = 18 + -27y Combine like terms: 27y + -27y = 0 6x + 0 = 18 + -27y 6x = 18 + -27y Divide each side by '6'. x = 3 + -4.5y Simplifying x = 3 + -4.5y
| 0.5x-0.4x-2=70-3.5x | | 48x^2+96x=0 | | 3x^2(2x^2+5)= | | x^2-9x=-13 | | 4x-6=10-2(x-1) | | 3x^2+42x=150 | | (6x+7)(7x-6)=0 | | -13.00+2.00=11 | | 2x^2-8x=7 | | 0.01-0.01(x+1)=-0.03(4-x) | | 2x=-2x^2+4 | | 3x-2x+4-x+x=60 | | 2x^2-7x=-4 | | -4x=-2x^2+30 | | 7-2x=11-6x | | 3x=577 | | 2x^2-7x=8 | | -6+4=40 | | 0=4x^3-56x | | 5x=11x+4 | | 20x+8=-8x^2 | | (x-10)2/5=(9x)1/5 | | 2x^2-11x=-2 | | 8w-13=3 | | 2-2x^3+4x^2-x=0 | | 3n-14=1 | | 3x^2-3x=3 | | -10x=-4x^2+24 | | 2(m)+l=1263 | | 2x^3+4x^2-x-2=0 | | 20x+4=-16x^2 | | 2x^3+4x^2-x=0 |